The ethical journalist making responsible decisions in the digital age - Foreman, Gene; Biddle, Daniel R.; Lounsberry, Emilie 1954-; Jones, Richard G. (Richard Gordon) 1971- (Wiley & Sons, Inc., 2022)
A new edition of this well-regarded, student-friendly text book for journalism ethics that addresses the challenges of digital-age journalism"--